2019
DOI: 10.20448/journal.522.2019.53.397.402
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spiritual Intelligence and Optimistic on Creativity in Team and Individual Sports Activities of Trabzon University Students

Abstract: The main purpose of this research was to investigate the effect of spiritual intelligence and optimistic on creativity of team and individual athletes of Trabzon University. In order to measure the spiritual intelligence, the optimism and the creativity variable, the standard questionnaires (Amram and Dryer, 2008), (Webber and Smokowski, 2018) and (Torrance, 2000) were used respectively. The reliability of the questionnaires was also evaluated by Cronbach's alpha test, respectively. The Cronbach's alpha coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The correlation table show the significance relationship among the elements of the intelligence and exhibit that each independent variable has significant relationship with the dependent variable, academic performance. This result is in line with EQ studies done by previous scholar [12,20] and also parallel with SQ studies done by other researchers [23,28]. Regression analysis was run through SPSS and simple check the independent relationship with dependent.…”
Section: Inferential Statisticssupporting
confidence: 90%
See 1 more Smart Citation
“…The correlation table show the significance relationship among the elements of the intelligence and exhibit that each independent variable has significant relationship with the dependent variable, academic performance. This result is in line with EQ studies done by previous scholar [12,20] and also parallel with SQ studies done by other researchers [23,28]. Regression analysis was run through SPSS and simple check the independent relationship with dependent.…”
Section: Inferential Statisticssupporting
confidence: 90%
“…Makes the person spontaneous, compassionate, competitive and resilience; develops positive interactive culture, integrated positive workforce, sense of community and  ISSN: 2252-8822 continuous learning among workforce [2,27]. Citizenship behaviors are developed among students, who accept academic norms and values and tries to promote them [28,29]. It empowers students, develop their confidence, lead them towards self-development and self-actualization, polish their skill, give them integrity, harmony, enthusiasm, direction, new philosophy of life and keep them healthy mentally and physically [20,30].…”
Section: Issn: 2252-8822 mentioning
confidence: 99%
“…Decisions made are necessary in a good emotional and spiritual state because all decisions made will have a great impact on the organization. If these two components are neglected, then it can weaken the spirit, confidence and cooperation among employees (Aydin, 2019). In the organization, most of the laborers or workers are transformed into schematic workers and pay less attention to spiritual and creative aspects (Vladimirovna, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This understanding not only expands the discourse on EC but also offers practical insights into fostering an environment conducive to emotional and spiritual growth, thus potentially unlocking unprecedented levels of creativity and innovation in the workplace. A study involving students at Trabzon University who participated in team and individual sports revealed that Emotional Intelligence (EI) and Spiritual Intelligence (SI) are factors in increasing creativity (Aydin, 2019). Another study suggested that SI can predict emotional resilience and creativity with insight into challenges and mindfulness serving as significant predictors (Hassan, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the type of sports, creative thinking gains more or less importance. Despite the artistic orientations of some individual sports, the need for creative development within team sports can be easily spotted [ 23 , 24 ]. It is not to be confused the athlete’s expert decision-making skills and their creative ability, which represent divergent and convergent thinking [ 21 ].…”
Section: Introductionmentioning
confidence: 99%